2020
DOI: 10.1007/s42729-020-00198-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Stimulates Antioxidant System and Osmotic Adjustment in Soybean Under Drought Stress

Abstract: The target of the present study was to determine the effect of nitric oxide (NO) on drought stress amelioration in soybean plant. Plants were treated with different polyethylene glycol (PEG) concentrations (0, 5, 10, and 15%) without or with NO (100 μM). Based on our results, drought stress significantly decreased growth in soybean plants. Increase in hydrogen peroxide, malondialdehyde, and aldehyde content indicated drought-induced oxidative stress in soybean plants. Drought stress enhanced the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 49 publications
6
57
0
Order By: Relevance
“…It has been reported that NO increased the accumulation of phenolic compounds, including total phenol, flavonol, and tocopherol, in soybean when exposed to water deficit conditions [55]. Both important phenolic biosynthetic enzymes, PAL and TAL, were also highly expressed by NO treatment [55]. Similar findings were reported in drought-stressed broccoli [31] and wheat [82].…”
Section: The Involvement Of No In the Antioxidant Systemsupporting
confidence: 75%
See 1 more Smart Citation
“…It has been reported that NO increased the accumulation of phenolic compounds, including total phenol, flavonol, and tocopherol, in soybean when exposed to water deficit conditions [55]. Both important phenolic biosynthetic enzymes, PAL and TAL, were also highly expressed by NO treatment [55]. Similar findings were reported in drought-stressed broccoli [31] and wheat [82].…”
Section: The Involvement Of No In the Antioxidant Systemsupporting
confidence: 75%
“…If drought becomes severe, the reduced rate of chloroplast ATP synthesis increases the mitochondrial respiration rate, which eventually induces the accumulation of more ROS in the mitochondria [ 54 ]. In plants, increased lipid peroxidation (MDA); lipoxygenase (LOX) activity; aldehyde, proline, cysteine, and electrolyte leakage; and hydrogen peroxide (H 2 O 2 ) production have been used to assess the increase of ROS production under drought [ 55 ]. Several Calvin–Benson cycle enzyme activities, such as RuBisCo, GAPDH, and phosphoribulokinase, have also been shown to be affected by drought stress [ 56 ].…”
Section: No and Drought Stressmentioning
confidence: 99%
“…While Sinkovič et al [27] associate an increase in the amount of polyphenols content with a higher content of organic matter and nitrogen, and with a lower amount of minerals. The characteristic chemical composition of the black soil mentioned (especially the high nitrogen content and organic matter) is a factor that has been shown an increase of the activity of the enzyme phenylalanine ammonia-lyase PAL [28]. This enzyme has an important role in the biosynthesis of polyphenols in the species of the genus Capsicum, and is responsible of the phenylalanine being transformed to 4-coumaril-CoA, a compound that is later used as a precursor in the synthesis of other polyphenolic compounds present in peppers like naringenin, quercetin, kaempferol, apigenin and luteolin [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Nipponbare grown under 20% PEG-induced hyperosmotic stress [ 93 ]. Rezayian et al [ 94 ] observed significantly increased MDA, H 2 O 2 content, and LOX activity in 15% PEG-stressed Glycine max plants compared with control samples. Rady et al [ 95 ] exposed Solanum lycopersicum L. cv.…”
Section: Oxidative Stress Under Abiotic Stressmentioning
confidence: 99%